Comparative effect of different pathogens on the condition of dysbiosis in rat kidneys - A. P. Levitsky; I. A. Selivanskaya; V. T. Stepan; P. I. Pustovoit; B. T. Stepan; N. A. Stepan (Kazimierz Wielki University, 2020)
Aim. Compare the effect of different pathogens on the development of kidney dysbiosis. Methods. The pathogens used were hydrazine sulfate, prednisolone, cyclophosphamide, lincomycin, and lipopolysaccharide (LPS). The condition of kidney dysbiosis was assessed in rats by a decrease in lysozyme activity and an increase in urease activity. Results. A decrease in the activity of lysozyme in the kidneys under the action of pathogens was established, which, when calculated per 1 mg of a pathogen, is hundreds of times stronger in LPS. All pathogens cause an increase in urease activity in the kidneys, which, when calculated per 1 mg of a pathogen, is hundreds of times stronger in LPS. A similar effect is exerted on the degree of dysbiosis, determined by the ratio of the relative activities of urease and lysozyme. Conclusion. All pathogens (except lincomycin) cause the development of dysbiosis in the kidneys, due to the possible bacteriolysis of tissue gram-negative bacteria with the release of LPS.